Frozen Section Library: Bone - Hameed, Omar. (Frozen Section Library,, 2011)
Frozen sections are performed while a patient is undergoing surgery as a basis for making an immediate diagnosis that will impact treatment decisions. Frozen section diagnosis is often a highly demanding situation for the pathologist who must render a diagnosis quickly for the patient and surgeon. The Frozen Section Library series will provide concise, user-friendly, site specific handbooks that are well illustrated and highlight the pitfalls, artifacts and differential diagnosis issues that arise in the hurried frozen section scenario. Omar Hameed, M.D., is an Assistant Professor, Department of Pathology, University of Alabama at Birmingham, Birmingham, Alabama, USA. Shi Wei, M.D.,Ph.D., is an Assistant Professor, Department of Pathology, University of Alabama, Birmingham, Alabama, USA. Gene P. Siegal, M.D., Ph.D., is a Robert W. Mowry Endowed Professor of Pathology & Director, Division of Anatomic Pathology; Executive Vice-Chair of Pathology - UAB Health System; Sr. Scientist, UAB Comprehensive Cancer Center & the Gene Therapy Center, Department of Pathology, University of Alabama at Birmingham, Birmingham, Alamaba, USA.   Gene P. Siegal, M.D., Ph.D., is a Robert W. Mowry Endowed Professor of Pathology & Director, Division of Anatomic Pathology; Executive Vice-Chair of Pathology - UAB Health System; Sr. Scientist, UAB Comprehensive Cancer Center & the Gene Therapy Center, Department of Pathology, University of Alabama at Birmingham, Birmingham, Alamaba, USA.   Gene P. Siegal, M.D., Ph.D., is a Robert W. Mowry Endowed Professor of Pathology & Director, Division of Anatomic Pathology; Executive Vice-Chair of Pathology - UAB Health System; Sr. Scientist, UAB Comprehensive Cancer Center & the Gene Therapy Center, Department of Pathology, University of Alabama at Birmingham, Birmingham, Alamaba, USA.  .